(untitled) (International Seven Journal of Multidisciplinary, 2026)
Agoraphobia, currently recognized as an independent diagnostic entity, is characterized by intense fear and avoidance of situations in which escape is perceived as difficult or help unavailable. This disorder causes profound functional impairment, affecting approximately 2% of adolescents and presenting high rates of comorbidities and suicide risk. This narrative review analyzes recent scientific evidence on the management of agoraphobia, emphasizing the integration of pharmacotherapy and Cognitive-Behavioral Therapy (CBT). In the pharmacological domain, Selective Serotonin Reuptake Inhibitors (SSRIs) are established as first-line treatment, while the use of benzodiazepines should be restricted to the acute phase to avoid inhibition of therapeutic habituation. In the psychotherapeutic field, exposure techniques remain the gold standard, enhanced by technological innovations such as Virtual Reality Exposure Therapy (VRET) and self-guided digital interventions. The study also highlights the relevance of metacognitive beliefs in the maintenance of the disorder. It is concluded that a multidisciplinary and technologically integrated approach is essential to break the cycle of avoidance and promote sustained functional recovery.